Extruder Path Analysis in Fused Deposition Modeling Using Thermal Imaging - Cañero-Nieto, Juan Miguel; Campo Campo, Rafael José; Díaz Bolaño, Idanis Beatriz; Solano-Martos, José Francisco; Vergara, Diego; Ariza-Echeverri, Edwan; Deluque-Toro, Críspulo (MDPI, 2025)
Fused deposition modeling (FDM) is one of the most widely adopted additive manufacturing (AM) technologies due to its accessibility and versatility; however, ensuring process reliability and product quality remains a significant challenge. This work introduces a novel methodology to evaluate the fidelity of programmed extruder head trajectories and speeds against those executed during the printing process. The approach integrates infrared thermography and image processing. A type-V ASTM D638-14 polylactic acid (PLA) specimen was fabricated using 16 layers, and its G-code data were systematically compared with kinematic variables extracted from long-wave infrared (LWIR) thermal images. The results demonstrate that the approach enables the detection of deviations in nozzle movement, providing valuable insights into layer deposition accuracy and serving as an early indicator for potential defect formation. This thermal image–based monitoring can serve as a non-invasive tool for in situ quality control (QC) in FDM, supporting process optimization and improved reliability of AM polymer components. These findings contribute to the advancement of smart sensing strategies for integration into industrial additive manufacturing workflows.
Keywords: Procesos de fabricación - Innovaciones tecnológicas; Infrared Thermography (IRT); Process Monitoring; In Situ Quality Control; Extruder Path Analysis; Polylactic Acid (PLA); Additive Manufacturing (AM); G-Code